2015
DOI: 10.1007/s00405-015-3625-6
|View full text |Cite
|
Sign up to set email alerts
|

Two rare cases of laryngeal intralymphatic histiocytosis

Abstract: We report two rare cases of intralymphatic histiocytosis causing, respectively, recurrent and persistent episodes of upper airway swelling and breathing difficulties. Case 1 was a 39-year-old man who was referred with recurrent upper airway swelling causing difficulty in breathing. A direct laryngoscopy was performed under general anesthesia due to minimal effect from treatment with antibiotics and anti-oedema medication. On examination, the larynx was found to be swollen and oedematous but not inflamed. Biops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In 2014, a group of Korean authors described a case of ILH involving the buccal mucosa of a 35-year-old Korean woman, which clinically mimicked oral lymphangioma circumscriptum. 20 Two additional ILH cases of noncutaneous ILH in the head and neck area were reported in 2014 by Reznitsky et al 21 Both patients were male, 39 and 35 years old and were found to have swelling of the laryngeal area. Biopsies in both cases revealed aggregates of histiocytes in the lumen of submucosal dilated blood vessels consistent with ILH.…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, a group of Korean authors described a case of ILH involving the buccal mucosa of a 35-year-old Korean woman, which clinically mimicked oral lymphangioma circumscriptum. 20 Two additional ILH cases of noncutaneous ILH in the head and neck area were reported in 2014 by Reznitsky et al 21 Both patients were male, 39 and 35 years old and were found to have swelling of the laryngeal area. Biopsies in both cases revealed aggregates of histiocytes in the lumen of submucosal dilated blood vessels consistent with ILH.…”
Section: Discussionmentioning
confidence: 99%
“…Discussion | Primary ILH of the larynx has, to our knowledge, only been described in 2 (male) patients before. 6 These patients had very similar clinical presentations, with persistent swelling of the epiglottis and aryepiglottic folds, and without cutaneous manifestations. Likewise, exacerbations of laryngeal swelling were described, 6 which even required 1 patient to be admitted to the intensive care unit.…”
Section: Persistent Laryngeal Swelling Caused By Primary Intralymphat...mentioning
confidence: 89%
“…Primary ILH of the larynx has, to our knowledge, only been described in 2 (male) patients before . These patients had very similar clinical presentations, with persistent swelling of the epiglottis and aryepiglottic folds, and without cutaneous manifestations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation